El dolor frente a la muerte como referencia de una propuesta pictórica expresionista contemporánea en Loja, a partir de la segunda década del siglo XXI - Loayza Ochoa, Victor Hugo (2018)
The present research work entitled "PAIN IN THE FACE OF DEATH AS A REFERENCE FOR A CONTEMPORARY EXPRESSIONIST PICTORIAL PROPOSAL IN LOJA, FROM THE SECOND DECADE OF THE 21ST CENTURY" has as main objective to present several pictorial works with aesthetic and philosophical quality, the same that refer to pain in the face of death, therefore it has been considered convenient to analyze the works of two referents of expressionism that support the personal work; Studies were also carried out on the human figure through photographs, quick drawings and sketches that were recorded in a work book related to death and tragedy that surrounds expressionism, thus allowing the development of artistic sensitivity to achieve a plastic proposal. Finally the works are disseminated through a collective exhibition called "Daily stories expressed from a contemporary artistic thought". In order to achieve the proposed objectives, the deductive method starts with the basic concepts about the tragedy surrounding the expressionism in such a way that it concludes in particular concepts as a means to represent emotions; On the other hand, the inductive method allowed for an in-depth analysis of the works of two Expressionist referents in order to generate a plastic proposal.